The evolution of swimming science research: content analysis of the “Biomechanics and Medicine in Swimming” Proceedings Books from 1971 to 2006 - Barbosa, Tiago M. (2018)
Swimming seems to be one of the sports more studied . More than one decade ago, Clarys (1996) made an content analysis of the research about swimming. However, in these last 13 years several developments happened in the aqua/c ac/vi/es. In the past swimming research was dedicated almost exclusively to compe//ve swimming. Nowadays there are several other aqua/c ac/vi/es being prac/ced in swimming centers, such as, Aqua/c exercises, Aqua/c Rehabilita/on, Infant swimming, etc. Swimming research is also dedicated to analyze and understand all these aqua/c ac- /vi/es. So, we hypothesized that data reported by Clarys (1996) may be out of date.